A descriptive study to quantify severity in patients with severe scrub typhus in hilly city of Northern India - Nadda, Nishant; Chauhan, Nidhi; Mahajan, Anjali; Chaudhary, Ankit; Katoch, Kritika; Chamotra, Shaina (International Journal of Advances in Medicine, 2019)
Background: Himachal Pradesh is an endemic area for scrub typhus. If not treated early, it can lead to life threatening complications. Therefore, more emphasis needs to be laid on the diagnosis and prompt treatment, so that mortality due to severe scrub typhus can be prevented. So, this study was done with an objective to study the clinical profile of patients diagnosed with severe scrub typhus and assess their severity using APACHE II score in IGMC, Shimla. Methods: Authors conducted a descriptive cross-sectional study in Indira Gandhi Medical College, Shimla over one year (June 2016-May 2017). Out of 538 confirmed scrub typhus cases, 58 severe cases were reported, and their severity was assessed with predefined criteria of sepsis and APACHE II score. Results: Mean age of males (50.18±18.6 yrs) was found to be more than that of females (45.52±14.5 yrs), the difference being statistically insignificant t(56)= -1.01, (P=0.32). Fever (100%), headache (84.5%), vomiting (79.3%) were the major presenting symptoms and tachycardia (96.5%), hypotension (87.9%), tachypnoea (94.8%) were the main clinical signs. The mean APACHE II score on admission was 16.25±5.0 with a predicted mortality of 23.5%, that was found to be less than actual reported hospital mortality (25.8%). Conclusions: APACHE II score was found reliable tool for risk stratification. Case fatality in diagnosed cases of severe scrub typhus was found high. Early diagnosis and prompt treatment according to guidelines would help in decreasing the mortality, financial burden on patient, society and health system.